2006
DOI: 10.1002/mus.20665
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the natural history of adult‐onset acid maltase deficiency by nutrition and exercise therapy

Abstract: Adult-onset acid maltase deficiency is an inherited lysosomal skeletal-muscle disease characterized by progressive myopathy and respiratory failure, for which there is no known therapy. In an uncontrolled, prospective study, we evaluated whether adherence to high-protein and low-carbohydrate nutrition and exercise therapy (NET) can slow the progressive deterioration of muscle function in this disease. Thirty-four patients have been treated with NET for periods of 2-10 years (mean 4.5 Ϯ 2.5). Pre-NET rate of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 31 publications
3
122
0
6
Order By: Relevance
“…Disease severity was assessed using the modified Walton scale. 14 The neurologists who collected the clinical data (S.R., B.B., F.G.) were unaware of ACE polymorphism status.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease severity was assessed using the modified Walton scale. 14 The neurologists who collected the clinical data (S.R., B.B., F.G.) were unaware of ACE polymorphism status.…”
Section: Patientsmentioning
confidence: 99%
“…We compared the distribution of the ACE genotypes in relation to the following parameters: sex; age; age of onset of the disease (i.e., patients were invariably asked about the onset of motor/respiratory difficulties in running/climbing stairs and/or rising from a chair); disease duration (from the above symptoms onset to actual age); serum creatine kinase (CK) levels, both at the time of diagnosis and at the latest follow-up (in view of the retrospective nature of our study, the information about CK levels at diagnosis was unavailable in 3 of 38 cases); severity of the disease, using the modified Walton scale 14 ; presence of scoliosis; symptoms of fatigue, as assessed by the Fatigue Severity Scale 17 ; presence of muscle pain, as assessed by a Visual Analogic Scale (only pain at rest/during exercise was considered, whereas pain related to muscle cramps/fatigue was excluded); body mass index (BMI); 6-minute walking test (6MWT); signs of fatigue during the 6MWT, defined as oxygen desaturation Ն5% or heart rate increase Ն20%; vital capacity, expressed both as percentage and in liters; and range of disease manifestations, with annotation of prevalence of respiratory versus muscular involvement or lack of a prevailing pattern.…”
Section: Analysis Of Clinical Featuresmentioning
confidence: 99%
“…Solium et al reported 2 out of 34 patients with acute onset respiratory insufficiency as the initial symptom 5 . Respiratory involvement may be more severe than skeletal muscle involvement 4 .…”
Section: Discussionmentioning
confidence: 99%
“…A sum score ranging from 0 to 40 was calculated for each patient by bilateral examination of shoulder abductors, elbow flexors, hip flexors and knee extensors. The stage of the disease was assessed by the modified Walton scale [3]. Pulmonary function was assessed by spirometry in the upright and supine position, and the maximum value of three reproducible tests was assessed for analysis.…”
Section: Methods and Resultsmentioning
confidence: 99%